Remote Learning : Evidence from Nepal during COVID-19 - Radhakrishnan, Karthika; Sabarwal, Shwetlena; Sharma, Uttam; Cullen, Claire; Crossley, Colin; Letsomo, Thato; Angrist, Noam (World Bank, Washington, DC, 2021)
This note discusses early results from a distance education program on foundational numeracy for primary school students in Nepal during Coronavirus (COVID-19) evaluated in a randomized trial. The trial included 3,700 households with children in public school (grades 3-5). It provided support for foundational numeracy through mobile phone-based tutoring. The trial tested delivery through public school teachers and also through NGO facilitators. It led to a 30 percent increase in foundational numeracy, with teachers being slightly more effective at producing learning gains than NGO facilitators. These results suggest that instructional support through mobile phones can be a high-access and low-cost approach to providing instruction at scale